Reproductive Biology of Yellowfin Tuna (Thunnus albacares) in Tropical Western and Central Pacific Ocean - Xiaofei Shi; Jian Zhang; Xiao Wang; Yixi Wang; Cheng Li; Jiangao Shi (Fishes, 2022)
A total of 756 yellowfin tuna (Thunnus albacares) caught by a Chinese drifting longliner in the tropical western and central Pacific Ocean (WCPO) from May 2018 to March 2019 were investigated to describe the reproductive biology of the species. Generalized linear model and polytomous logistic regression for the ordinal response model were employed to assess the effects of biometric and spatiotemporal factors (such as individual fork length (FL), fishing depth, dissolved oxygen, and month) on the reproductive traits of yellowfin tuna. The results showed that FLs ranged from 87 to 163 cm, averaging 115.8 cm (SD = ±14.2) for females and 121.8 cm (SD = ±16.8) for males. The proportion of males in the sampled fish was 0.61 (SD = ±0.29), and larger males (>130 cm) were proportionally predominant. Analyses based on the monthly variation of the gonadosomatic index and monthly proportion of sexual maturity stages of the gonads showed that the main spawning period of yellowfin tuna lasts from September to December. In addition, the 50% first maturity FLs of males and females were 111.96 cm (SD = ±1.04) and 119.64 cm (SD = ±1.30), respectively. This study provides new information on the reproductive development of T. albacares in the tropical WCPO region. These reproductive parameters reduce uncertainty in current stock assessment models, which will ultimately assist the fishery in becoming sustainable for future generations.